1988
DOI: 10.3171/jns.1988.68.1.0062
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance to enteral feeding in the brain-injured patient

Abstract: Calorie and protein supplementation improves nutritional status. This support may improve outcome and decrease morbidity and mortality in acutely brain-injured patients. Investigators have observed a poor tolerance to enteral feedings after brain injury and have noted that this persists for approximately 14 days postinjury. This delay has been attributed to increased gastric residuals, prolonged paralytic ileus, abdominal distention, aspiration pneumonitis, and diarrhea. In the present investigation, 23 brain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(56 citation statements)
references
References 18 publications
1
48
0
7
Order By: Relevance
“…However, patients with TBI often have severe impairment of gastrointestinal passage despite the use of different therapies to improve tolerance for enteral feeding. In some patients, parenteral or supplemented nutrition (enteral feeding with parenteral components on top to reach the required nutrition goals) has to be applied (Norton et al 1988). A later supplementation may be associated with a better outcome than early supplementation (Casaer et al 2011).…”
Section: Way Of Feedingmentioning
confidence: 99%
“…However, patients with TBI often have severe impairment of gastrointestinal passage despite the use of different therapies to improve tolerance for enteral feeding. In some patients, parenteral or supplemented nutrition (enteral feeding with parenteral components on top to reach the required nutrition goals) has to be applied (Norton et al 1988). A later supplementation may be associated with a better outcome than early supplementation (Casaer et al 2011).…”
Section: Way Of Feedingmentioning
confidence: 99%
“…(32)(33)(34) However, enteral nutrition has been reported to be more beneficial than parenteral nutrition, given its lower cost, lower infection risk, protection of intestinal epithelium integrity, improvement of immunocompetence and attenuation of the metabolic stress response during the illness critical phase. (35) Some severe HT patients, however, cannot tolerate enteral nutrition and show increased gastric residues, prolonged paralytic ileus, abdominal distension and diarrhea. (35) In this clinical condition, enteral nutrition success appears to be inversely correlated with the ICP and trauma severity.…”
Section: Nutrition Support For Acute Brain Injury Patientsmentioning
confidence: 99%
“…(35) Some severe HT patients, however, cannot tolerate enteral nutrition and show increased gastric residues, prolonged paralytic ileus, abdominal distension and diarrhea. (35) In this clinical condition, enteral nutrition success appears to be inversely correlated with the ICP and trauma severity. The mechanism of this relationship may be multi-factorial.…”
Section: Nutrition Support For Acute Brain Injury Patientsmentioning
confidence: 99%
“…Motility disorders in brain injured patients include gastroesophageal reflux related to reduced tone in the lower esophageal sphincter and deferred gastric emptying [8,9]. Some studies showed that moderate TBI with no substantial mucosal damage causes a delayed significant decrease in intestinal contractile activity that occurs primarily in the ileum due to decreased contraction amplitude.…”
Section: Tbi and Gi Problemsmentioning
confidence: 99%
“…The association between the severity of brain injury and the intolerance of enteral feeding suggests a strong link between the central nervous system and the nonfunctional gut [6,7]. More than 50% of patients with severe head injuries do not tolerate enteral feedings [8]. The intolerance is presented by vomiting, abdominal distention, delayed gastric emptying [9], esophageal reflux [10], and decreased intestinal peristalsis indicating that GI dysfunction is a common phenomenon following TBI [11].…”
Section: Traumatic Brain Injury (Tbi) Is a Noteworthy General Medicalmentioning
confidence: 99%